Macrophage Polarization and Its Role in Liver Disease - Wang, Cheng; Ma, Cheng; Gong, Lihong; Guo, Yuqin; Fu, Ke; Zhang, Yafang; Zhou, Honglin; Li, Yunxia (Frontiers in Immunology, 2021)
Macrophages are important immune cells in innate immunity, and have remarkable heterogeneity and polarization. Under pathological conditions, in addition to the resident macrophages, other macrophages are also recruited to the diseased tissues, and polarize to various phenotypes (mainly M1 and M2) under the stimulation of various factors in the microenvironment, thus playing different roles and functions. Liver diseases are hepatic pathological changes caused by a variety of pathogenic factors (viruses, alcohol, drugs, etc.), including acute liver injury, viral hepatitis, alcoholic liver disease, metabolic-associated fatty liver disease, liver fibrosis, and hepatocellular carcinoma. Recent studies have shown that macrophage polarization plays an important role in the initiation and development of liver diseases. However, because both macrophage polarization and the pathogenesis of liver diseases are complex, the role and mechanism of macrophage polarization in liver diseases need to be further clarified. Therefore, the origin of hepatic macrophages, and the phenotypes and mechanisms of macrophage polarization are reviewed first in this paper. It is found that macrophage polarization involves several molecular mechanisms, mainly including TLR4/NF-κB, JAK/STATs, TGF-β/Smads, PPARγ, Notch, and miRNA signaling pathways. In addition, this paper also expounds the role and mechanism of macrophage polarization in various liver diseases, which aims to provide references for further research of macrophage polarization in liver diseases, contributing to the therapeutic strategy of ameliorating liver diseases by modulating macrophage polarization.